C–O isotope geochemistry of the Dashiqiao magnesite belt, North China Craton: implications for the Great Oxidation Event and ore genesis. (28th January 2013) - Tang, Hao‐Shu; Chen, Yan‐Jing; Santosh, M.; Zhong, Hong; Wu, Guang; Lai, Yong
Abstract : The worldwide 2.33−2.06 Ga unique positive δ 13 Ccarb excursion has been correlated with the Great Oxidation Event (GOE). The Dashiqiao Formation in the Liaohe Group of the northeastern North China Craton formed at 2.2−2.174 Ga and hosts one of the world‐class magnesite deposits. Here we present major element and C and O isotope analyses of 22 samples from the Dashiqiao Formation and use the data to evaluate the impact of the GOE in the North China Craton, as well as the genesis of the Dashiqiao giant magnesite deposits. Six dolomitic marble samples from a 600 m thick interval with 1.10 ± 0.04 of MgO/CaO (mol) ratios show higher δ 13 CPDB values of 0.6−1.4‰ (average 1.2 ± 0.3‰) than those of normal marine carbonates over the globe. However, they display lower δ 18 OSMOW of 16.4−19.5‰ (average 18.2 ± 1.1‰) as compared to their contemporaneous counterparts, suggesting that the primary carbonates in the Dashiqiao Formation should possess a positive δ 13 C anomaly (possibly 4.2‰) reflecting the impact of the GOE, and that the δ 13 C and δ 18 O values have been depleted in post‐sedimentation diagenesis and/or regional metamorphism. The >550 m thick magnesite layer in the studied section has MgO/CaO ratios ranging from 4.45−200.00. These rocks show δ 13 C and δ 18 O values of 0.1−0.9‰ and 9.2−16.9‰, with average values of 0.4 ± 0.2‰ and 13.3 ± 2.5‰, respectively, obviously lower than those of the underlying dolomites. The depletions of 13 C and 18 O in magnesites relative to dolomitic marbles are interpreted to be the result of hydrothermal alteration related to regional metamorphism leading to rock recrystallization and mass exchange. This interpretation is further confirmed from the hanging‐wall dolomitic marble and the veinlet‐filled magnesite from the ore layer. The former contains mega‐crystals of cylindrical talc and has δ 13 C of −2.6‰ and δ 18 O of 14.1‰, indicating that a local fluid–rock interaction between (argillaceous) dolomite and (siliceous) hydrothermal fluids poor in 13 C and 18 O resulted in the formation of talc and further depletion both in δ 13 C and in δ 18 O. The veinlet‐filled magnesite yields δ 13 C and δ 18 O values of −2.7‰ and 16.2‰, respectively, showing lower δ 13 C but higher δ 18 O than those of massive magnesite in the adjacent strata. Our observation thus strongly supports the interpretation that the massive magnesite interacted with low‐δ 13 C fluids which were possibly sourced from meteoric water at low temperature during post‐ore time. Thus, the formation of the Dashiqiao magnesite deposits involved primary sedimentation, diagenesis, regional metamorphism, hydrothermal replacement and local post‐ore fluid–rock interaction. Copyright © 2013 John Wiley & Sons, Ltd.